Dynamic and hybrid phase shift controller for dual active bridge converter - Narasimha, S.; Surender Reddy, S. (International Journal of Engineering and Technology, 2019)
This paper proposes a dynamic dual active bridge (DAB) converter and a hybrid phase shift control (HPSC) scheme for a (0.5-1) variation in the voltage conversion ratio. The proposed HPSC scheme is a combination of extended phase shift (EPS) and triple phase shift (TPS) modulations. It also provides a simple closed-form implementation for the primary and secondary-side phase-shift angles. During the light load operation of dynamic DAB converter, the TPS modulation is employed such that the practical zero voltage sequence operation can be extended to zero load. For heavy loads, the secondary-side phase-shift angle decreases to zero, hence the EPS modulation is applied. In this paper, the MATLAB Simulink software is used with an input voltage range of (200-400)V and then the output voltage wave forms are investigated for both EPS and TPS modulations for different operating modes of buck and boost operations.Â Â Â